A Novel Crosslinking Method for Improving the Anti-Calcification Ability and Extracellular Matrix Stability in Transcatheter Heart Valves - Qi, Xiaoke; Jiang, Zhenlin; Song, Mingzhe; Tang, Zhenjie; Xie, Xinlong; Liu, Yuhong; Wu, Qiying; Wu, Zhongshi (Frontiers in Bioengineering and Biotechnology, 2022)
More than 200,000 patients with aortic diseases worldwide undergo surgical valve replacement each year, and transcatheter heart valves (THV) have been more widely used than ever before. However, THV made by the glutaraldehyde (Glut) crosslinking method has the disadvantage of being prone to calcification, which significantly reduces the durability of biomaterials. In this study, we applied a novel crosslinking method using ribose in THV for the first time, which can decrease calcification and increase the stability of the extracellular matrix (ECM). We incubated the bovine pericardium (BP) in ribose solution at 37°C by shaking for 12 days and confirmed that the structure of the BP was more compact than that of the Glut group. Moreover, the ribose method remarkably enhanced the biomechanical properties and provided reliable resistance to enzymatic degradation and satisfactory cellular compatibility in THV. When the BP was implanted subcutaneously in vivo, we demonstrated that ECM components were preserved more completely, especially in elastin, and the immune-inflammatory response was more moderate than that in the Glut treatment group. Finally, the ribose-cross-linked materials showed better anti-calcification potential and improved durability of THV than Glut-cross-linked materials.